SERIAL IMAGING OF A CHILD WITH LEGG-CALVE-PERTHES DISEASE AT BETHESDA HOSPITAL, YOGYAKARTA: A CASE REPORT - Jourdy Kharisma Pradnyana (Faculty of Medicine Universitas Kristen Duta Wacana, 2020)
Background: Legg-Calve-Perthes disease (LCPD) is a rare condition of idiopathic avascular necrosis of the femoral head, mostly affects children under fifteen old. Most cases only affect one femoral head; bilateral involvement only occurs in about 15% of cases. Early diagnosis and prompt intervention play an important role in the prognosis to prevent degenerative damage on the bones and joints. Objective: To describe a case of Legg-Calve-Perthes disease in a 9-year-old boy in Bethesda Hospital, Yogyakarta. Case Description: A 9-year-old boy came with one month history of worsening pelvic pain to Bethesda Hospital, Yogyakarta. He also showed limping and limited mobility. Initial imaging studies did not find any abnormalities. Further follow-up with MSCT scan related to the complaint of persistent pain showed defects of left hip joint indicating Legg-Calve-Perthes disease. The patient undergone skin traction treatment which shows modest improvement on serial radiographic examinations during hospital admission. Conclusion: The rarity of LCPD warrant thorough imaging studies on children with unexplainable severe hip joint pain. Treatment should be initiated as early as possible after diagnosis to prevent further bone damage and worsening prognosis. Conservative management with skin traction would benefit the patient in restoring normal anatomy and optimal joint congruence to prevent degenerative damage to the joints.